Retssag 1689 ved Fleskum og Hornum Herredsting - Nielsen, Adolf Sommer (Kirkehistoriske Samlinger, 1988)
The article discusses a dispute between the vicar of Gudum parish, Peder Jensen Helsingør (1603-1693) and the curate, Niels Michelsen Tæbring (1657-1713). This lawsuit is recorded in 1689 at the Fleskum and Hornum Herredsting (district court), and the dispute is over the question of who had the right to the tithes from two derelict farms. Some contracts between the two clergymen are given in the article which illustrate the powers held by the vicar in the administration of his benefices. In reality, and on his own initiative, he divided the parish of Gudum-Lillevorde in two, so that in effect he and the curate each had their own parish. In conclusion, a different interpretation than hitherto is given of signatures with the letters »mpp«.